Design considerations of ASBGo++ (Plus Plus) Smart Walker - Alves, Joana (2017)
The development of a gait disorder leads to the loss of the ability to walk and may cause dependence of others in daily life, which is a major determinant in life quality. Thus, devices that provide mobility assistance and ambulatory daily exercises are essential for the health and life quality of such individuals. The ASBGo Smart Walker is an academic project aimed to create a medical solution for rehabilitation of patients with gait disorders. Based on the acquired know-how, the physicians, physiotherapist and patients’ feedback, a new prototype, named ASBGo++ (Plus Plus) was developed, mechanically and electronically improved. This paper will focus on the proposed mechanical, design and ergonomic considerations, enhancing the positive aspects of this smart walker and emphasizing the features that are most highlighted in its design, structure, and functionality.